Appropriate and acceptable health assessments for people experiencing homelessness - Susan Jayne Gordon; Nicky Baker; Margie Steffens (BMC, 2022)
Abstract Background Appropriate and acceptable recruitment strategies and assessment tools are essential to determine the health needs for people experiencing homelessness. Based on a systematic review and known feasible community-based health assessments for people who are not homeless, a set of health assessments were trialled with people experiencing homelessness. Methods Participants were recruited via support agencies. They completed a health risk assessment, demographic and self-report health questionnaires, and objective assessments across 17 domains of health. Results Fifty-three participants (43.3% female, mean age 49.1 years) consented and completed 83-96% of assessments. Consent was reversed for assessments of grip, foot sensation, body measures (11%), and walking (30%), and initially refused for stress, sleep, cognition (6%); balance, walk test (9%) and oral examination (11%). There was one adverse event. Most assessments were both appropriate and acceptable. Some required modification for the context of homelessness, in particular the K10 was over-familiar to participants resulting in memorised responses. Recruitment strategies and practices must increase trust and ensure participants feel safe. Conclusions This set of health assessments are appropriate and acceptable for administration with people experiencing homelessness. Outcomes of these assessments are essential to inform public and primary health service priorities to improve the health of people experiencing homelessness.